2018
DOI: 10.4172/neuropsychiatry.1000404
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Thyroid Status, Cortisol Level, Cognition And Neuropsychiatric Symptoms In Patients With Alzheimer Disease

Abstract: Objective: Growing evidence suggests an association between alterations in thyroid function and cortisol level and the pathogenesis and progression of Alzheimer disease (AD). The aim of this study was to investigate whether these hormones are related to the cognitive and neuropsychiatric manifestations in the patients with AD.Methods: This was a cross-sectional, case control study. Cortisol level and thyroid status were evaluated in 40 outpatients with mild to moderate AD and 20 normal controls, and cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…After carefully scanning the titles and abstracts, 39 articles that were potentially eligible for inclusion were retrieved. After reading the full texts, 28 articles were excluded for the following reasons: nine studies were not cohort or case-control studies 18 19 20 21 22 23 24 25 26 ; 13 lacked usable data 13 14 17 27 28 29 30 31 32 33 34 35 36 ; four had different study purposes 37 38 39 40 ; one did not perform FT4 and TSH measurements 41 ; and one was a replicate study with a shorter follow-up 42 than that by de Jong et al 10 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After carefully scanning the titles and abstracts, 39 articles that were potentially eligible for inclusion were retrieved. After reading the full texts, 28 articles were excluded for the following reasons: nine studies were not cohort or case-control studies 18 19 20 21 22 23 24 25 26 ; 13 lacked usable data 13 14 17 27 28 29 30 31 32 33 34 35 36 ; four had different study purposes 37 38 39 40 ; one did not perform FT4 and TSH measurements 41 ; and one was a replicate study with a shorter follow-up 42 than that by de Jong et al 10 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that in TD in adults, particularly in hypothyroidism, there are deficits in cognitive functions that are reversible with hormone replacement (DE SOUZA et al, 2016;ZHANG et al, 2012). However, magnetic resonance imaging studies correlate hyperthyroidism with decreased hippocampus and amygdala volumes and the onset of dementia (DE JONG et al, 2006), while other studies have associated prolonged use of T4 with the onset of AD, once TH can regulate the generation of APP isoforms (HARPER; ROE, 2010).…”
Section: Thyroid Hormones and Energy Homeostasis In The Brainmentioning
confidence: 99%
“…The thyroid function has a central role in both neurodevelopment process and neurodegenerative processes. It is suggested in recent years that the thyroid function is linked to the AD; it has been proposed that the thyroid dysfunction enhances the risk of AD by a direct harmful effect of thyroxine discharge on cholinergic neurons; however, whether the neuropathological mechanism of altered thyrotropin levels happens before or after the beginning of AD is unclear (Zhang, Du, Wang, & Cheng, 2012). Treatment with THs can remarkably improve cognition and emotional indices in patients (Bunevicius, 2009).…”
Section: Ad and Thyroid Functionmentioning
confidence: 99%